Understanding of Taxation, Taxpayer Morality, and Tax Compliance in Indonesia: The Importance of Tax Awareness - Oktris, Lin; Muktiasih, Indri; Azhar, Zubir (AKRUAL: Jurnal Akuntansi, 2024)
Introduction/ Main Objective: This study aims to analyze the influence of tax understanding and taxpayer morality on tax compliance with tax awareness as a moderating variable. Background Problems: Tax compliance is a crucial aspect of an effective and sustainable taxation system. However, tax compliance levels are often influenced by various factors, including tax understanding and taxpayer morality. On the other hand, tax awareness is considered a factor that can either strengthen or weaken the relationship between tax understanding and morality with tax compliance. Research Methods: This study employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to taxpayers in several major cities in Indonesia. The sample consists of 100 respondents selected randomly. The collected data were analyzed using multiple regression techniques and moderation analysis to test the research hypotheses. Finding/ Results: The results show that tax understanding has a positive and significant influence on tax compliance. Additionally, taxpayer morality is also found to have a positive and significant influence on tax compliance. Conclusion: Taxpayers with high morality tend to be more aware of their tax obligations and are more compliant in reporting and paying taxes. Taxpayers with a good understanding of tax regulations and provisions tend to be more compliant in fulfilling their tax obligations.